Coinfection of gonorrhea and chlamydia trachomatis: A case report - Anita Indah Sari; Idrianti Idrus; Safruddin Amin; Muji Iswanty; Anni Adriani; Muhlis (Journal of Pakistan Association of Dermatologists, 2023)
Gonorrhea (GO) is the most common sexually transmitted infection (STI) caused by Neisseria gonorrhoeae (NG). In Indonesia, the GO sequence is the highest of STI diseases. GO in men can cause urethritis, while women are usually asymptomatic. Chlamydia is caused by Chlamydia trachomatis bacteria. Men infected with Chlamydia typically present with urinary tract inflammation, fever, penile discharge, and severe testicular pain. Male urethritis is a coping disease that presents purulent or mucopurulent discharges through the urethra, sometimes accompanied by dysuria. Gonorrhea urethritis is the most common venereal disease today and can be found worldwide. Timely treatment and choosing the right medicine at the right dose can eliminate the infection, prevent complications, prevent further spread, and avoid the development of drug resistance. We reported a case of gonorrhea urethritis in a 25-year-old man with a complaint of yellow-whitish discharge from the opening of the penis. The diagnosis was established based on the Gram staining, culture, PCR tests. The patient was treated with azithromycin and cefixime, resulting in clinical improvement. Â 